Effective Deep Learning Model to Identify Harmful Bacteria in Blood Samples for Healthcare Application - et al., Dr. G. Naveen Sundar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Like water, blood is also an important part of human life. It is the basic and most necessary life-sustaining system of most organisms as well as humans. The basic functionality of blood is to nourish the organs and provide essential nutrients required by the system. The contamination of blood has a very harmful and invasion effect in human as well as other organisms’ life. To tackle this situation of identifying the contaminants of blood (mainly bacteria and pathogens), we are trying to come up with a deep learning model, which can identify various bacteria and pathogens in the blood samples, thus saving many lives.